Effects of Postural Education Program (PEPE Study) on Daily Habits in Children - Aina Maria Galmes-Panades; Josep Vidal-Conti (Frontiers in Education, 2022)
The current randomized controlled trial aimed to investigate the effects of a postural education program on daily life habits related to low back pain (LBP) in children. Reducing the disease burden of unspecific LBP in children is of major public health relevance, as children with episodes of LBP tend to experience chronic back pain in adulthood. The study was performed in Majorca (Spain), with 253 primary school children aged between 10 and 12 years. The sample was selected from different clusters (schools) using convenience sampling and randomly distributed into an experimental group (5 schools) or a control group (5 schools). Individual postural items did not improve after the intervention in the experimental group, nor did they improve in the control group. Neither did they improve postural habits score in both groups after the intervention. In conclusion, this telematic intervention has not managed to improve postural habits in children. Nevertheless, there is a lack of evidence to determine whether it is feasible to carry out telematics intervention that promotes lifestyle changes in children.